Chitinolytic enzymes from Clostridium aminovalericum: activity screening and purification - Simůnek, J; Tishchenko, G; Rozhetsky, K; Bartonová, H; Kopecný, J; Hodrová, B (Folia microbiologica, 2004)
A strain isolated from the feces of takin was identified as Clostridium aminovalericum. In response to various types of chitin used as growth substrates, the bacterium produced a complete array of chitinolytic enzymes: chitinase ('endochitinase'), exochitinase, beta-N-acetylglucosaminidase, chitosanase and chitin deacetylase. The highest activities of chitinase (536 pkat/mL) and exochitinase (747 pkat/mL) were induced by colloidal chitin. Fungal chitin also induced high levels of these enzymes (463 pkat/mL and 502 pkat/mL, respectively). Crab shell chitin was the best inducer of chitosanase activity (232 pkat/mL). The chitinolytic enzymes of this strain were separated from culture filtrate by ion-exchange chromatography on the carboxylic sorbent Polygran 27. At pH 4.5, some isoforms of the chitinolytic enzymes (30% of total enzyme activity) did not bind to Polygran 27. The enzymes were eluted under a stepwise pH gradient (pH 5-8) in 0.1 mol/L phosphate buffer. At merely acidic pH (4.5-5.5), the adsorbed enzymes were co-eluted. However, at pH close to neutral values, the peaks of highly purified isoforms of exochitinases and chitinases were isolated. The protein and enzyme recovery reached 90%.
Keywords: Acetylglucosaminidase; glykosidhydrolasy; Clostridium; Glycoside Hydrolases; Chitinases; izoenzymy; zvířata; chitin; Goats; chromatografie iontoměničová; chitinasy; Animals; kozy; Substrate Specificity; Chitin; Isoenzymes; Enzyme Induction; feces; acetylglukosaminidasa; Amidohydrolases; amidohydrolasy; substrátová specifita; enzymová indukce; Feces; Chromatography, Ion Exchange